Quality recognition and prediction : smarter pattern technology with the Mahalanobis-Taguchi system - Teshima, Shoichi; Hasegawa, Yoshiko; Tatebayashi, Kazuo, 1948- (The Momentum Press digital library, 2012)
The MT system is a diagnostic and predictive method for analyzing patterns in multivariate data that has provided benefits in many diverse applications over the past decade or so. It has proven itself superior in many cases to more traditional artificial intelligence applications such as neural nets.